A cross-country time and motion study to measure the impact of electronic medication management systems on the work of hospital pharmacists in Australia and England. (September 2019) - Westbrook, Johanna I.; Li, Ling; Shah, Sonal; Lehnbom, Elin C.; Prgomet, Mirela; Schofield, Behnaz; Cresswell, Kathrin; Slee, Ann; Coleman, Jamie J.; McCloughan, Lucy; Sheikh, Aziz
Highlights: Australian and English pharmacists' work patterns significantly differed at baseline. Electronic medication management systems changed the work patterns of pharmacists. The same magnitude of effect on pharmacists' work in each country was found. Cross-country studies help understand how systems integrate in different contexts. Abstract: Background: Qualitative studies have provided important insights into how hospital pharmacists' work changes when electronic medication management (EMM) systems are introduced. Quantitative studies of work practice change are rare. Despite the use of EMM systems internationally, there are no cross-country comparative studies of their impact on health professionals' work. We aimed to quantify and compare the type and magnitude of changes in hospital pharmacists' work pre- and post-EMM implementation in two countries. Methods: Parallel, direct observational, time and motion studies of pharmacists in Australia and England pre- and post-EMM implementation. 20 pharmacists were observed: 9 in an Australian 440-bed hospital (155 h); and 11 pharmacists in a 500-bed English hospital (258 h). The Work Observation Method By Activity Timing (WOMBAT) software was used to collect observational data. Proportions of observed time in 11 tasks by study period (pre- versus post-EMM) and site, time spent with others or alone, and using different tools (e.g computers, paper) were calculated. Magnitude of changes between pre- and post-EMM by task and country were determined using z-tests for proportions adjusting for multiple testing. Results: At baseline, Australian and English pharmacists spent the greatest proportion of time in medication review. Post-EMM, time in medication review (Australia 21.6%–27.5%; England 27.1%–33.8%) and history-taking (Australia 7.6%–13.3%; England 19.5%–28.9%) significantly increased. Despite country differences in these tasks at baseline, the magnitude of changes did not significantly differ. English pharmacists increased time engaged in medication discussions with patients post-EMM (from 5.9% to 10.8%; p = 0.01). The Australian rate did not change (18.0%–27.2%; p = 0.09), but was higher at baseline. Post-EMM, Australian pharmacists spent 63.4% of time working alone, compared to 92.0% for English pharmacists. Conclusions: EMM systems impacted the same core areas of work and had a similar magnitude of effect on pharmacists' work in both countries. Anticipated reductions in medication review and history taking were not observed.